Manajemen Bandwidth Menggunakan Metode Hirarchical Token Bucket (HTB) Pada Pembatasan Kecepatan Internet (Studi kasus: SMK Al-Muslim) - Muhammad Rafi Ilyasa K; Arip Solehudin; Didi Juardi (Peneliti.net, 2021)
Bandwidth management is a network concept in which bandwidth is set to get a flat and structured internet connection. Therefore, bandwidth management is needed in the Al-Muslim Vocational School Lab so that students can study conducively without obstacles in doing learning in the Lab. Bandwidth management in the Lab uses the HTB method. so that it can allocate bandwidth according to bandwidth requirements Bandwidth management at the Al-Muslim Vocational School with a research methodology (PPDIOO) (Prepare, Plan, Design, Implement, Operate, Optimize), the results obtained by measuring the QoS (Quality of Service) parameter using the HTB method at the Al-Vocational Vocational School Lab. Muslim